SOEKARNO DAN ARGUMEN TEOLOGIS-FILOSOFIS DALAM PEMIKIRAN ISLAM - Imam Sukardi (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2019)
Soekarno was an important figure in Indonesia. He was one of founding fathers for the establishment of the Unitary State of Republic Indonesia. Soekarno was able to affirm his views on the establishment of a democracy-based state, in the difficult political dynamics with the emergence of pressure from groups that wants to establish an Islamic state. This paper wants to see how Soekarnoâ€™s philosophical views of Islamic teachings and their application are ideal for the Indonesian Muslim community. In the context of theology, Soekarno saw that Indonesian Muslims could not yet understand their religion properly and correctly. Muslims experience delays in realizing the ideals of a nation state based on Islamic values as a result of the failure to capture the spirit of islam. Public awareness about the essence of religion still tends to be shallow and fanatical. Soekarno proposed the idea of rationality of religious text, in order to be able to capture the value of religious teaching.Â